The project manager's desk reference : a comprehensive guide to project planning, scheduling, evaluation, and systems - Lewis, James P., 1941- (New York : McGraw-Hill, 2000)
Introduction and overview. Project planning. Project scheduling. Project control and evaluation. Cuases of project success and failure. Other issues in project management. Resources and references.
Keywords: Management; Industrial project management; Industrial development projects -- Management; Scheduling (Management)